The Relationship Between Basic Technique and Arm Strength and Swimming Speed in Adolescent Athletes - Azhar Nur Salimah; Tatang Muhtar; Muhammad Nur Alif; Anggi Setia Lengkana (Journal of Physical Education Health and Sport, 2026)
Freestyle swimming speed is one of the main indicators of achievement of swimming athletes, especially in adolescent athletes who are still in the development stage of technical skills and physical condition. Mastery of basic techniques and arm muscle strength are important factors that can affect the effectiveness of movement and swimming speed, but they do not necessarily develop in a balanced manner in every athlete. This study aims to determine the relationship between mastery of basic techniques and arm muscle strength at freestyle swimming speed in adolescent athletes. The research method used is a quantitative approach with a correlational design. The research sample amounted to 20 adolescent athletes who were selected using purposive sampling techniques. Data collection was carried out through testing and measurement, namely assessment of basic techniques using observation sheets, measurement of arm muscle strength through physical tests, and measurement of swimming speed using a 50-meter swimming time. Data were analyzed using descriptive and inferential statistics with the Spearman correlation test because some data were not distributed normally. The results showed that there was a positive and significant relationship between mastery of basic techniques and arm muscle strength (r = 0.467; p < 0.05). In addition, arm muscle strength also had a positive and significant relationship with freestyle swimming speed (r = 0.450; p < 0.05). However, the relationship between mastery of basic technique and swimming speed showed a positive but not statistically significant relationship (r = 0.320; p > 0.05). These findings suggest that arm muscle strength has a more dominant role in increasing swimming speed than partial basic technique. The conclusion of this study is that freestyle swimming speed in adolescent athletes is influenced by a combination of mastery of basic technique and arm muscle strength. Therefore, an integrated and balanced training program between improved technique and muscle strength is indispensable to achieve optimal swimming performance.